Mega-Event Organization Considering Safety, Security and Resilience: Insights from the Milan World Expo 2015 and London Olympic and Paralympic Games 2012 - Atun Girgin, Funda; Edizel Tasci, Ozlem (TeMA - Journal of Land Use, Mobility and Environment, 2019)
Cities become globally significant and attract national and international interest from all over the world with the help of mega-events, such as World EXPO and the Olympic Games. Mega-events highly require the involvement of various actors working together for the same overall purpose, although these actors have the responsibility of diverse target groups and require to use different resources. In his paper, we aim to understand the role of organizations in mega-events in relation to the socio-technical systems they operate. We consider security, safety and resilience articulated in six areas: planning, construction of the site, training, collaboration, communication and legacy, in three different time slots: before, during and after the event. Results include insights to enhance multi-organizational culture-based practice. The field studies conducted in Milan in 2015 and 2016 on Milan World EXPO 2015, and in London in 2012 and 2016 on the London Olympic and Paralympic Games 2012. The research findings are based on the experience of the real actors involved in these two events. The findings suggest several courses of action for decision-makers and emergency planners to safety and security design strategies that can facilitate resilience as a legacy of a mega-event.